2006
DOI: 10.2214/ajr.04.1868
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Function in Multi-Ethnic Study of Atherosclerosis: Normal Values by Age, Sex, and Ethnicity

Abstract: The normal LV differs in volume and mass between sexes and among certain ethnic groups. When indexed by body surface area, LV mass was independent of age for both sexes. Studies that assess cardiovascular risk factors in relationship to cardiac function and structure need to account for these normal variations in the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
388
4
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(412 citation statements)
references
References 33 publications
17
388
4
3
Order By: Relevance
“…This is consistent with the sex associated difference in LV mass reported in the ASE guidelines (21% on average for linear dimensions) as well as by large population based studies such as The Multi-Ethnic Study of Atherosclerosis (21%), the Asklepios Study (21%) or the general population study of Devereux et al (22%). 13,21,22 This consistent percentage suggests that if a population based study finds a significantly greater than 20% difference in LV mass indexed to BSA between sexes, one has to question whether a body size composition bias may have been introduced. Consistent with our finding, a recent study by Pressler et al also observed no sex M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 8 related differences in LV mass indexed to LBM in athletes participating in low to moderate intensity sports.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is consistent with the sex associated difference in LV mass reported in the ASE guidelines (21% on average for linear dimensions) as well as by large population based studies such as The Multi-Ethnic Study of Atherosclerosis (21%), the Asklepios Study (21%) or the general population study of Devereux et al (22%). 13,21,22 This consistent percentage suggests that if a population based study finds a significantly greater than 20% difference in LV mass indexed to BSA between sexes, one has to question whether a body size composition bias may have been introduced. Consistent with our finding, a recent study by Pressler et al also observed no sex M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 8 related differences in LV mass indexed to LBM in athletes participating in low to moderate intensity sports.…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with previous studies, we have also found that female have a lower mass to volume ratio suggesting more eccentric remodeling. 21 This however assumes that mass and volume should be scaled using the same allometric indexing. If we use the different allometric coefficient for volume found in our study and the study of George et al, the sex differences in remodeling pattern disappears or reverse between sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac magnetic resonance imaging was performed at the baseline visit using scanners with 1.5‐T magnets, a 4‐element, phased‐array surface coil placed anteriorly and posteriorly, ECG gating, and brachial artery blood pressure (BP) monitoring 30. All images were read centrally and left ventricular mass determined as previously described 30, 38…”
Section: Methodsmentioning
confidence: 99%
“…Comparisons between ethnicities may require larger sample sizes, with samples of less than 10 participants needed for LV mass/BSA, septal wall thickness and LV posterior wall thickness among one study [28]. A priori sample size calculations based on another investigation suggest that ethnic differences may be identified with as few as 8 participants per ethnic group for LV mass, and as few as 22–23 participants per ethnic group for stroke volume and LV mass/BSA [12]. …”
Section: Methodsmentioning
confidence: 99%